Antimicrobial Activity of Pome granataumÃ¢â¬â¢s Endophytic Bacteria Against Pathogenic Microbe - Putri Alfianti Sriwinahyu; Prapti Sedijani; Lalu Zulkifli (Jurnal Biologi Tropis, 2020)
White pomegranate (Punica granatum L.) is one of potential plant that can be use as an antimicrobial. The objective of this study was to determine antimicrobial activity of endophytic bacteria from white pomegranate (Punica granatum L.) in inhibiting the growth of pathogenic microbia (Staphylococcus aureus, Streptococcus viridans, Shigella dysentriae, Klebsiella pneumoniae and Fusarium sp. fungi). The stages of the research were isolation endophytic bacteria, antimicrobial assay, and characterization of potential endophytic bacterial. Endophytic bacterial were isolated from bark, leaves, flower, and fruit peel of white pomegranate taken from Gebang Baru, Mataram District. Antimicrobial assay was then performed using agar diffusion method, using supernatant of endophytic bacteria, water as negative control or ciprofloxacin as positive control. The potential isolates were characterized using Gram staining and biochemical test. The results showed that 2 endophytic bacterial isolates (DNX2 and BNG1) show strong activity against S. aureus, 3 endophytic bacterial isolates (BTG1, DNX11, and BNG1) show strong activity against S dysentriae, and 1 isolate KLBX11 shows medium activity against Fusarium sp. fungi. Those isolates are gram-possitive with bacill-shaped and produce spores. It can be concluded that it is possible to obtain potential endophytic bacterial from white pomegranate are potential as an alternative source for antimicrobial compounds.